Lipid droplets as endogenous intracellular microlenses - Chen, Xixi; Wu, Tianli; Gong, Zhiyong; Guo, Jinghui; Liu, Xiaoshuai; Zhang, Yao; Li, Yuchao; Ferraro, Pietro; Li, Baojun (Light, science & applications, 2021)
Using a single biological element as a photonic component with well-defined features has become a new intriguing paradigm in biophotonics. Here we show that endogenous lipid droplets in the mature adipose cells can behave as fully biocompatible microlenses to strengthen the ability of microscopic imaging as well as detecting intra- and extracellular signals. By the assistance of biolenses made of the lipid droplets, enhanced fluorescence imaging of cytoskeleton, lysosomes, and adenoviruses has been achieved. At the same time, we demonstrated that the required excitation power can be reduced by up to 73%. The lipidic microlenses are finely manipulated by optical tweezers in order to address targets and perform their real-time imaging inside the cells. An efficient detecting of fluorescence signal of cancer cells in extracellular fluid was accomplished due to the focusing effect of incident light by the lipid droplets. The lipid droplets acting as endogenous intracellular microlenses open the intriguing route for a multifunctional biocompatible optics tool for biosensing, endoscopic imaging, and single-cell diagnosis.